Localization of spectrum and stability of certain classes of dynamical systems - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We develop a method for the localization of spectra of multiparameter matrix pencils and matrix functions, which reduces the problem to the solution of linear matrix equations and inequalities. We formulate algebraic conditions for the stability of linear systems of differential, difference, and difference-differential equations.